Students Feedback to Online Learning on Practice Courses - Suryo Prabowo; Mujiono Mujiono; Marisa Marisa (LPPM Universitas Terbuka, 2022)
This study aims to determine students feedback to the application of online learning on practical courses in the Education Technology Study Program. This research is a descriptive research with a quantitative approach. The research instrument used in the form of questionnaires and interviews. Of the 104 respondents who filled out the questionnaire, as many as 88 respondents (86.3%) still wanted a synchronous meeting in the form of a webinar tutorial. The results of the interviews showed that the application of online learning in practical courses received a positive response from the majority of respondents, but the implementation time and learning assessment received a negative response.